THE IMPACT OF PRICE, SERVICE QUALITY AND TRUST ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION IN AUTOMOTIVE INDUSTRY - Arya Asraf Danarkusuma; Eric Harianto; Nursaid Nursaid; J.E. Sutanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Increased mobility has influenced business development in the automotive sector, especially vehicle maintenance services. This development is different from the increase in business revenue in vehicle maintenance. This study aims to determine the effect of price, service quality and customer trust on customer loyalty through customer satisfaction. This research uses quantitative methods using probability sampling techniques with a simple random sampling approach. The number of samples in this study was 210 respondents. The data collection technique used a questionnaire and was analysed using Smart PLS. The results of this study indicate that price, service quality and customer trust significantly affect customer loyalty through customer satisfaction. Price have significant impact in customer satisfaction, it can be a reference to determining a price strategy and services quality that are affordable and better than competing companies.